Looking to northern Peru: The dawn of tourism in Piura. An analysis based on traveler´s guides, 1928-1960 - Vargas Pacheco, Cristina (2023)
In the 20th century, there is a gradual emergence of the tourism phenomenon in Peru. The equation that enables this involves state intervention, as well as various actors and factors, including mindsets. From this multifactorial perspective, the primary objective of this research is to approach the understanding of the beginnings of tourism in Piura. The chronological delineation of the period under consideration corresponds to the publication of two traveler’s guides that serve as conveyors of imaginaries about the Piura department, allowing us to contrast their continuities, changes, and permanence to the present. The first one corresponds to the «Guías Departamentales del Touring Club Peruano» (1928), and the second one, to the «Guía del Peregrino: Piura en 1960» (1960). This is a qualitative historical investigation involving the study of primary and secondary sources. The results indicate that the improvement of communication infrastructure and state support play a role in awakening the idea of tourism in the region. Both public and private actors converge in its development, and travelers’ attention to socio-cultural aspects results in the construction of an image of Piura, translating into a tourism offer for a destination with intangible heritage richness, which is also associated with sun and beach tourism.